Cultural Beliefs, Perceptions, and Experiences on Female Genital Mutilation Among Women and Men: A Qualitative Analysis - González-Timoneda, Alba (Journal of interpersonal violence, 2022)
The practice of female genital mutilation (FGM) is a deeply-rooted tradition that affects predominantly regions of Africa and Asia. Because of migration flows, FGM is an issue of increasing concern worldwide. FGM is now carried out in Europe, North America, Australia and New Zealand, and more specifically among immigrant communities from countries where it is common. This study aims to assess the experience, knowledge, attitudes, and beliefs related to FGM of migrant women and men from FGM-affected countries residing in Spain and the United Kingdom. A phenomenological qualitative approach was used. Participants (n=23) were recruited by using the snowball sampling technique until data saturation was reached. Data were collected through 18 open-ended interviews and a focus group. Of the 23 participants, 20 women had undergone FGM. The following five themes were generated from interviews: (a) FGM practice development, (b) knowledge about the practice, (c) reasons for performing FGM, (d) attitudes toward continuing or abandoning the practice, and (e) criminalization of FGM. The study here presented identifies a lack of information, memory, and knowledge about the practice of FGM and typology among women with FGM. The justification of the practice seems to be based on a multifactorial model, where sociocultural and economic factors, sexual factors, hygienic-esthetic factors, and religious-spiritual factors take on a greater role in the analysis of the interviews carried out. The participants practically unanimously agree to advocate the abandonment and eradication of this harmful traditional practice. The knowledge displayed in this study may provide a basis for improving awareness and healthcare in such collectives, aiming the eradication of this harmful traditional practice.